ALGORITHM OF WORK OAE REGISTRATION TOOL IN THE TWO MODES OF - Лебедев, Д. Ю. (Science-based technologies, 2014)
Objective methods OAE registration signals that are described in the work successfully used in modern audiology practice for screening hearing children. Used registration procedure "echo signal" on frequency distortion product and detained OAE caused that always appear and record in normal hearing children after acoustic stimulation of the organ of hearing person. Development of algorithms of the system of registration of otoacoustic emissions (OAE) in the signal acquisition transient evoked otoacoustic emission (ZVOAE) and otoacoustic emission signal at a frequency distortion product (SPOAE) for objective auditory screening method based on the signal recording OAE will make it possible to move to the next stage, creating software solutions. Measuring block and block of generation of acoustic stimuls for these algorithms are implemented based on a digital signal processor module StarterKit TMS320VC5510.